Maine’s Culture of Reuse and Its Potential to Advance Environmental and Economic Policy Objectives - Isenhour, Cindy; Crawley, Andrew; Berry, Brieanne; Bonnet, Jennifer (Maine Policy Review, 2017)
Policies designed to extend the lifetime of products—by encouraging reuse rather than disposal—are proliferating. Research suggests that reuse can ease pressure on natural resources and improve economic efficiency, all while preventing waste. In Maine, there are clear signs of a tradition of reuse that might be used to advance these goals. But beyond discrete observations, proverbs, and anecdotal stories, little data have been collected upon which to estimate the potential of Maine’s reuse economy. This paper draws upon findings generated during the first year of a five-year interdisciplinary, mixed-methods research project designed to explore the environmental, social, and economic dimensions of reuse in Maine. Our preliminary findings suggest that Maine does, indeed, have a vibrant but underestimated reuse economy. Less expected are findings that suggest reuse has promise to enhance economic resilience and contribute to culturally appropriate economic development.
Keywords: Maine; reuse; waste management